A High Temperature Polymer Electrolyte Membrane Fuel Cell Model for Reformate Gas - M. Mamlouk; Tiago Sousa; Keith Scott (International Journal of Electrochemistry)
A one-dimensional model of a high temperature polymer electrolyte membrane fuel cell using polybenzimidazole (PBI) membranes is described. The model considers mass transport through a thin film electrolyte covering the catalyst particles as well as through the porous media. The incorporation of a thin film model describing reactant gas mass transport through electrolyte covering the electrocatalyst is shown to be an essential requirement for accurate simulation. The catalyst interface is represented using a macrohomogeneous model. The influence of carbon monoxide, carbon dioxide, and methane, which would be present in a reformate gas, is considered in terms of the effect on the anode polarisation/kinetics behaviour. The model simulates the influence of operating conditions, cell parameters, and fuel gas compositions on the cell voltage current density characteristics. The model gives good predictions of the effect of oxygen and air pressures on cell behaviour and correctly simulates the mass transport behaviour of the cell. The model with reformate gas shows that additional voltage losses associated with CO poisoning can lead to loss in voltage of tens of mV and thus reduction in power.